Measuring Signal of Skill Mismatch from Online Job Advertisements and HR Roles: A conceptual paper - Zuria Akmal, Saad; Muhammad Ashraf, Fauzi; Naliza, Solat; Azmi, Salim (e-International Publishing House, 2023)
Skill mismatch remains an ongoing issue due to differences in qualitative interpretation and quantitative measurement. Scholars and practitioners have yet to reach a consensus on a definitive method for measurement, making it challenging to diagnose and solve the problem. This conceptual paper focuses on measuring skill mismatch signals through online job advertisements and the roles of HR in addressing this issue. It reviews relevant literature from journals, articles, and dissertations from previous studies. By enhancing online job advertisements and refining HR roles, this study aims to improve future labour market conditions.